Sphagnum cuspidatulum extract prevents acute kidney injury induced by high-fat diet and streptozotocin via alleviation of oxidative stress and apoptosis in pre-diabetic rats - Laorodphun, Pongrapee; Chaisen, Sutheera; Amattat, Sarocha; Maphet, Pornchita; Printrakul, Narin; Pandith, Hataichanok; Panya, Aussara; Kongmali, Burit; Swe, Myat Theingi; Arjinajarn, Phatchawan (Frontiers in Pharmacology, 2024)
On behalf of the author and co-authors, I would like to thank you and the editorial review board of Frontiers in Pharmacology, section Renal Pharmacology for giving us the opportunity to revise and resubmit our manuscript entitled "Sphagnum cuspidatulum extract prevents acute kidney injury induced by high-fat diet and streptozotocin via alleviation of oxidative stress and apoptosis in pre-diabetic rats", Manuscript ID: 1464463. The manuscript has been certainly benefited from very helpful suggestions.We have now carefully revised our manuscript according to the reviewer's comments and we have submitted a revised manuscript for your review.